On Cas A, Cassini, comets, and King Charles - Soria, Roberto; Balestrieri, R.; Ohtsuka, Y. (CSIRO, 2013)
We re-examine the long-standing problem of the date of the Cassiopeia A supernova (SN), in view of recent claims that it might be the 1630 ‘noon-star’ seen at the birth of King Charles II. We do not support this identification, based on the expected brightness of a Type-IIb SN (too faint to be seen in daylight), the extrapolated motion of the ejecta (inconsistent with a date earlier than 1650), the lack of any scientific follow-up observations, the lack of any mention of it in Asian archives. The origin of the 1630 noon-star event (if real) remains a mystery; there was a bright comet in 1630 June but no evidence to determine whether or not it was visible in daylight. Instead, we present French reports about a fourth-magnitude star discovered by Cassini in Cassiopeia in or shortly before 1671, which was not seen before or since. The brightness is consistent with what we expect for the Cas A SN; the date is consistent with the extrapolated motion of the ejecta. We argue that this source could be the long-sought SN.